Characterization of Full-Length Transcriptome Sequences and Splice Variants of Lateolabrax maculatus by Single-Molecule Long-Read Sequencing and Their Involvement in Salinity Regulation - Tian, Yuan; Wen, Haishen; Qi, Xin; Zhang, Xiaoyan; Liu, Shikai; Li, Bingyu; Sun, Yalong; Li, Jifang; He, Feng; Yang, Wenzhao; Li, Yun (Frontiers in Genetics, 2019)
Transcriptome complexity plays crucial roles in regulating the biological functions of eukaryotes. Except for functional genes, alternative splicing and fusion transcripts produce a vast expansion of transcriptome diversity. In this study, we applied PacBio single-molecule long-read sequencing technology to unveil the whole transcriptome landscape of Lateolabrax maculatus. We obtained 28,809 high-quality non-redundant transcripts, including 18,280 novel isoforms covering 8,961 annotated gene loci within the current reference genome and 3,172 novel isoforms. A total of 10,249 AS events were detected, and intron retention was the predominant AS event. In addition, 1,359 alternative polyadenylation events, 3,112 lncRNAs, 29,609 SSRs, 365 fusion transcripts and 1,194 transcription factors were identified in this study. Furthermore, we performed RNA-Seq analysis combined with Iso-Seq results to investigate salinity regulation mechanism at the transcripts level. A total of 518 transcripts were differentially expressed, which were further divided into 8 functional groups. Notably, transcripts from the same genes exhibited similar or opposite expression patterns. Our study provides a comprehensive view of the transcriptome complexity in L. maculatus, which significantly improves current gene models. Moreover, the diversity of the expression patterns of transcripts may enhance the understanding of salinity regulatory mechanism in L. maculatus and other euryhaline teleosts.